Ultrasonication-assisted enzymatic bioprocessing as a green method for valorizing oat hulls - Zhou Ying; Tian Ye; Beltrame Gabriele; Laaksonen Oskar; Yang Baoru (Elsevier, 2025)
Ultrasonication-assisted enzymatic treatments using Viscozyme®, Alcalase®, and feruloyl esterase were applied to recover proteins, avenanthramides, phenolic acids, free sugars, and organic acids from oat hulls (OH). The profiles of the chemical compounds in OH were markedly influenced by the nature of enzymes, ultrasonication frequency, and processing time. A significant increase in the contents of proteins and phenolic acids was observed in the liquid fraction of all enzymatic treatments, which was 2–19 folds higher than those detected in untreated OH. In contrast, avenanthramides were mostly degraded during enzyme hydrolyses. The highest content of proteins (68.9 g/100 g DM) was found in the liquid fraction after the feruloyl esterase treatment assisted with 90 min of ultrasonication at 25 kHz. This fraction also contained 0.07% phenolic acids, 14.1% free sugars, and 1.8% organic acids, which can be potentially used as the ingredient of novel food products.